"For a woman..." from Elsa Calcagno: a musical contribution to the peronist propaganda machinery. (Revista Argentina de Musicología, 2018)
“For a woman ... ", choral-symphonic piece written in 1953 by the Argentine composer Elsa Calcagno upon a Mario Mende Brun's poem, is an homage to Eva Perón after her death.  This work begins with an outline about the author's musical personality.  Later on it analyzes the complementary documentation about the creation and the first performance of the score and clears up the relation between music and text. Following Pierre Bourdieu in his cultural campus's notion, and Clifford Geertz in his studies about the relation between the nature of a power structure and its outward symbolic expressions, concludes that this production emphatically illustrates.